FATORES DE RISCO CARDIOVASCULAR: COMPARAÇÃO ENTRE OS GÊNEROS EM PACIENTES SUBMETIDOS A CIRURGIA CARDÍACA - Cruz, Thomé d.; Lorenzoni, Juliara C. W.; Fassbinder, ânia R. C.; Dallazen, Fernanda; Winkelmann, Eliane R.; Schneider, Juliana (Salão do Conhecimento, 2013)
Resumo